Efficacy of metformin monotherapy in newly diagnosed type 2 diabetes mellitus patients treated at Prince Mohammed Bin Abdulaziz hospital, Riyadh, Saudi Arabia - Aloufi, Mohammed; Makhlouta, Abdullatif; Alsibaee, Ahmad; Zaknoun, Naim; Aljohani, Razan; Mohammed, Moneer; Alotaibi, Asma; Alahamdi, Ghassan; Alkurdi, Abdullah A. (International Journal of Research in Medical Sciences, 2023)
Background: Metformin monotherapy is the primary therapeutic approach in most cases of newly diagnosed type 2 diabetes mellitus (T2DM) as it is safe, efficient, and is known to lower risks like vascular complications in patients. Previous studies have shown that glycemic control provided by metformin monotherapy is not consistent and needs to be monitored in association with other factors. Due to the complex nature of the disease and other factors like genetic predisposition, ethnicity, and geographic distribution, it is crucial to investigate its effect on the Saudi population. This study aimed to evaluate the glycemic response of metformin monotherapy in individuals with newly diagnosed T2DM who had not previously taken any other medications. Methods: A retrospective study model was followed to determine metformin monotherapy in newly diagnosed type 2 diabetes patients. The efficacy of the metformin monotherapy was evaluated in the patients who were drug naive and had undergone treatment for six months. Results: HbA1c levels for our study population (n=136) before and after metformin monotherapy for a period of six months was collected from patient records. The study cohort included both male (n=71) and female (n=67) patients. There was a significant difference in the HbA1c levels of all diabetes patients before (Mean=9.1, SD=2.84) and after (Mean=7.13, SD=1.51) medication; 2-tailed significance p<0.001. Conclusions: Metformin monotherapy was effective in reducing the HbA1c levels across both genders and all age groups in the present study. These results suggest that metformin monotherapy could be the first line of therapy for newly diagnosed T2DM individuals.